2010
DOI: 10.3168/jds.2009-2720
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between body condition score and reproduction traits in Canadian Holstein and Ayrshire first-parity cows

Abstract: The objective of this study was to investigate the genetic relationship between body condition score (BCS) and reproduction traits for first-parity Canadian Ayrshire and Holstein cows. Body condition scores were collected by field staff several times over the lactation in herds from Québec, and reproduction records (including both fertility and calving traits) were extracted from the official database used for the Canadian genetic evaluation of those herds. For each breed, six 2-trait animal models were run; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
(47 reference statements)
7
40
0
4
Order By: Relevance
“…Using a threshold model, the heritability of CR was estimated as 0.043 for firstparity Holstein cows in New York State. Jamrozik et al (2005), Tsuruta et al (2009) and Bastin et al (2010) estimated that the heritabilities of NR to 56 days at first lactation in Canadian Holstein cows were 0.020 and 0.026, respectively. Liu et al (2008) also reported that the heritabilities of NR to 56 days, as estimated from 25.5 million insemination records, were 0.012 for heifers and 0.015 for dairy cows in Germany, Austria and Luxembourg.…”
Section: Discussionmentioning
confidence: 99%
“…Using a threshold model, the heritability of CR was estimated as 0.043 for firstparity Holstein cows in New York State. Jamrozik et al (2005), Tsuruta et al (2009) and Bastin et al (2010) estimated that the heritabilities of NR to 56 days at first lactation in Canadian Holstein cows were 0.020 and 0.026, respectively. Liu et al (2008) also reported that the heritabilities of NR to 56 days, as estimated from 25.5 million insemination records, were 0.012 for heifers and 0.015 for dairy cows in Germany, Austria and Luxembourg.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic correlations between BCS and fertility are unfavourable (e.g. Pryce et al, 2001;Berry et al, 2003;Dechow et al, 2004;Bastin et al, 2010). BCS is generally visually or manually assessed by trained operators and only gives an approximate indication of a cow's (subcutaneous) energy reserves (Roche et al, 2009).…”
Section: Impact Of Selecting For Rfi On Other Traitsmentioning
confidence: 99%
“…Likewise, Mao et al (2004) found that heritability was greatest for BCS in early to midlactation in parity 1 and 2, whereas heritability was greatest later in lactation for parity 3. Bastin et al (2010) worked with the same full data set (before edits) as the current study and found a similar shape for the heritability curve for first-parity Canadian Holsteins, though with generally lower daily heritabilities. Berry et al (2003b) studied multiparous cows, and also modeled BCS using a random regression animal model.…”
Section: Short Communicationmentioning
confidence: 99%